STATISTICAL OPTIMIZATION OF MEDIA COMPONENTS FOR THE ENHANCED Β-XYLANASE AND Β-MANNANASE PRODUCTION FROM ASPERGILLUS NIGER C-5 VIA SOLID STATE FERMENTATION OF WHEAT BRAN - CHETNA JANVEJA,; SUSHEEL SINGH RANA,; SANJEEV KUMAR SONI, (International Journal of Pharma and Bio Sciences, 2016)
Hemicellulases are the key enzymes in the production of alternative fuels and chemicals from lignocellulosic biomass. The present study dealt with the statistical optimization of various fermentation parameters for enhancing the yields of β-xylanase and β-mannanase from Aspergillus niger C-5 using wheat bran based basal media. Plackett-Burman was first employed to screen out the important process parameters that have significant effect on the production of enzymes. Out of 23 variables screened, four variables including tryptone, SDS, NH4Cl, NaCl were selected to further study the interactive effects and optimum level of these variables in central composite design of response surface methodology. This combinatorial statistical approach led to the fine tuning of productivities revealing 5200 and 200 IU/g of β-xylanase and β-mannanase yields respectively. Hence, this two step optimization approach led to 3.72 and 2.08 fold increase in the activities of enzymes as compared to under unoptimized conditions.